Relative drought tolerance of major rainfed crops of the semiarid tropics - Singh, B.B.; Mai-Kodomi, Y.; Terao, T. (1999)
Ten crop species were evaluated for their relative drought tolerance at the seedling stage. Healthy seeds of each crop were planted in wooden boxes of 130 cm length, 65 cm width and 15 cm depth, filled with 3 soil types (river sand, loamy sand and sandy loam) and watered daily. A week after germination watering was stopped and the reaction to progressive water stress was observed. Based on percentage dead plants at various time intervals and days taken to 100% dead plants, soyabean (Glycine max) appeared the most drought susceptible and cowpea (Vigna unguiculata) the most drought tolerant. The overall ranking of the crops in the increasing order of drought tolerance was: soyabean < black gram (V. mungo) < green gram (V. radiata) < groundnut (Arachis hypogaea) < maize (Zea mays) < sorghum (Sorghum bicolor) < pearl millet (Pennisetum glaucum) < bambara nut (V. subterranea) < lablab bean (Lablab purpureus) < cowpea. The water stress induced using soil with a higher sand content was too severe for crops other than cowpea and lablab bean. With increased clay content and gradual water stress, it may be possible to use this method to detect varietal differences in less drought tolerant crops